If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 27 = 2x + 63 Reorder the terms: 27 + 5x = 2x + 63 Reorder the terms: 27 + 5x = 63 + 2x Solving 27 + 5x = 63 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 27 + 5x + -2x = 63 + 2x + -2x Combine like terms: 5x + -2x = 3x 27 + 3x = 63 + 2x + -2x Combine like terms: 2x + -2x = 0 27 + 3x = 63 + 0 27 + 3x = 63 Add '-27' to each side of the equation. 27 + -27 + 3x = 63 + -27 Combine like terms: 27 + -27 = 0 0 + 3x = 63 + -27 3x = 63 + -27 Combine like terms: 63 + -27 = 36 3x = 36 Divide each side by '3'. x = 12 Simplifying x = 12
| 10x+5=0 | | 4y^2+x+20y-12=0 | | 15-221-33-21 | | -5x/7-8 | | 30x-0.02x*2-50=0 | | c=30x-0.02x*2-50 | | -5/7-8-7 | | 10+g/-9=12 | | -25+t/2=50 | | table= | | 2x(x+4)=396 | | 4f+6=8t-14 | | 0=x^2-x-144 | | 2x^3-4x^2-6x=0 | | -2(w+(-6))=8w | | f/2-22=48 | | 7x+1.75=4x+3.10 | | 3b^2+12b+1=3 | | 18-3x=27 | | a/-8+15=23 | | N^2-16n+48=-9 | | 7+1.75x=4+3.10x | | X^2+14x-38=8 | | 41=6m-7 | | 2x^2+8x+14=8 | | z-9z=4z-6-z | | 55=-7y+6 | | 4p^2+16p-23=-9 | | R^2-18r+14=-3 | | -3t+9=-21 | | 25/m-m/5+m | | 18-.50y=3+.50y |